Differential contribution of α2δ auxiliary subunits of voltage-gated calcium channels in mouse models of pain and itch - Joao M. Braz; Madison Jewell; Karnika Bhardwaj; Sian Rodriguez-Rosado; Veronica Craik; Allan I. Basbaum (PLoS ONE, 2025)
Voltage-gated calcium channels (VGCCs) are multimeric proteins composed of alpha 1, β and γ subunits, as well as one of four auxiliary α2δ subunits. Although there is considerable preclinical and clinical evidence for a contribution of VGCCs to nociceptive processing, notably the gabapentin-targeted α2δ-1 subunit, unclear is the extent to which other α2δ subunits contribute to baseline or injury-altered pain and itch processing. Here, we investigated the anatomical and behavioral consequences of deleting α2δ-2, α2δ-3 or α2δ-4 in the mouse and report that selectively ablating each α2δ subunit leads to different, and in some cases, opposite effects on behavioral indices of pain and itch. Specifically, deleting α2δ2 resulted in mechanical and heat hypersensitivity, and an increase in spinal cord microglial immunoreactivity, but reduced scratching (presumptive) itch in response to a pruritogen. In contrast, ablation of α2δ3 led to thermal hyposensitivity, but no change in mechanical responsiveness or indices of itch. Mice deficient for α2δ4 exhibited hyposensitivity across pain modalities and only minor itch deficits. Interestingly, these differential effects were limited to baseline nociceptive responses, therefore we conclude that the α2δ-2, α2δ-3 and α2δ-4 subunits of VGCCs differentially contribute to pain and itch processing. The mechanisms underlying these differences remain however to be determined.